NEOGENE STRUCTURES OVERPRINTING PALAEOZOIC THRUST SYSTEMS IN THE ANDEAN PRECORDILLERA AT 30°S LATITUDE - Alvarez-Marron J.; Brown D.; Rodriguez-Fernandez R.; Heredia N.; Busquets P.; Colombo F. (My University, 2006)
Field studies along a 30°S latitude transect of the Precordillera in NW Argentina indicate that Neogene to recent deformation caused high-angle faulting that uplifted and breached a Palaeozoic east-verging thrust stack. Palaeozoic structures crop out in the higher linear ranges, and intramontane Neogene basins occur in the intervening valleys. The Palaeozoic rocks include three tectonic units with contrasting structural styles and differences in stratigraphy. The Western Allochthon includes elastic Ordovician rocks metamorphosed to lower greenschist facies and folded by large-scale asymmetric, east-verging folds with a well-developed axial planar cleavage. This unit overthrusts a Siluro-Devonian flysch-type succession of the Central Imbricate thrust system and associated fault propagation folds in which the thrusts merge into a basal thrust beneath Ordovician carbonates. Middle to Upper Carboniferous sediments unconformably overlie structures of this imbricate system. In the Frontal Unit minor thrust faults are interpreted to explain the low-angle unconformity within Palaeozoic rocks. Neogene deformation causes only a minor overprint of the Palaeozoic structure, and large-scale folding in the Frontal Unit appears to be mostly of Neogene age. The new data indicate that Neogene intracontinental shortening may be smaller than previously proposed, providing new perspectives on the present orogenic architecture along this Andean section.
Keywords: Neogene; Carboniferous; Devonian; Ordovician; Cenozoic::Neogene; Кайнозой::Неоген; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская; Paleozoic::Ordovician; Палеозой::Ордовикская